El crecimiento económico y la pobreza en la región La Libertad, 2005 - 2015 - Sánchez Paredes, Kevin Martín (2019)
In this research the impact of economic growth on poverty in the region La Libertad, period 2005-2015, because much talk about economic growth and its impact on poverty is analyzed, for which you want to check whether the theory meets for the case of the La Libertad region. This investigation was motivated by the lack of investigations of local interest existing in our region. For this, a good analysis should be carried out, with empirical evidence, which helps to make better decisions as to what should be invested in our region to reduce poverty effectively and efficiently. After the analysis it was found that according to the monetary approach for each of the provinces of the La Libertad region, there is a causality between economic growth and poverty. Where, economic growth has a positive impact on the reduction of the poverty rate in the La Libertad region, in the period 2005-2015.